2010
DOI: 10.1111/j.1471-8847.2008.00239.x
|View full text |Cite
|
Sign up to set email alerts
|

Ethical Problems in Conducting Research in Acute Epidemics: The Pfizer Meningitis Study in Nigeria as an Illustration

Abstract: The ethics of conducting research in epidemic situations have yet to account fully for differences in the proportion and acuteness of epidemics, among other factors. While epidemics most often arise from infectious diseases, not all infectious diseases are of epidemic proportions, and not all epidemics occur acutely. These and other variations constrain the generalization of ethical decision-making and impose ethical demands on the individual researcher in a way not previously highlighted. This paper discusses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 3 publications
0
33
0
Order By: Relevance
“…In the context of a public health urgency or emergency, clinical trials may be impossible or unethical . The primary obligation of public health and disease control professionals is to make the outbreak stop, or failing that, to minimize morbidity and mortality to the best of their ability, using tools at their disposal.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the context of a public health urgency or emergency, clinical trials may be impossible or unethical . The primary obligation of public health and disease control professionals is to make the outbreak stop, or failing that, to minimize morbidity and mortality to the best of their ability, using tools at their disposal.…”
Section: Discussionmentioning
confidence: 99%
“…In the context of a public health urgency or emergency, clinical trials may be impossible or unethical. 21,22 The primary obligation of public health and disease control professionals is to make the outbreak stop, or failing that, to minimize morbidity and mortality to the best of their ability, using tools at their disposal. In this context, it is impossible to know with certainty what the epidemiological "counterfactual" would have been in this case; that is, we cannot know what the contour of this outbreak would have been if aggressive antiviral drug use had not been initiated in this community.…”
Section: Discussionmentioning
confidence: 99%
“… 52 It also includes situations of very high insecurity; despite their connections with local communities, if a circumstance is deemed unsafe for health personnel it is likely not substantially safer for anthropologists. 53 In a similar vein, just as health campaigns have been poorly managed, misused or abused, 54 55 so the clumsy or unethical use of anthropology can poison perceptions and cause psychological or physical harm. 38 The misuse or misrepresentation of anthropology, in ignorance of professional codes of conduct, can have real consequences for individuals and health interventions.…”
Section: What Is Anthropology Not Good For?mentioning
confidence: 99%
“…The Nigerian community has participated in a number of HIV prevention trials, some of which were sub optimal and led to sensitivities and mistrust such as the failed Pfizer trials of 1996 which was reported to lack IRB and NAFDAC approvals and had no documented evidence of informed consent [21,22]. However, prevention trials such as the microbicide study, a phase III double blinded randomized placebo controlled trial, approved by relevant IRBs and NAFDAC was conducted in Lagos and Port-Harcourt between 2004 and 2007 according to good clinical practice as established by the International Conference on Harmonization (ICH) [23].…”
Section: Past Effortsmentioning
confidence: 99%